PENGARUH KEGIATAN BERDZIKIR TERHADAP PERILAKU KEAGAMAAN SANTRI DI PONDOK PESANTREN RIYADLUL JANNAH PACET MOJOKERTO - Ahmad Prawoto; Mahmud Fauzi (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
Dzikir, which means remembering, can normatively have a good effect, namely to make the heart calm. A peaceful heart is one of the characteristics of mental health. At the Pondok Pesantren Riyadlul Jannah Pacet Mojokerto, there are quite a lot of dzikir and routine activities, including Wirid Yasin, Wirdul Latif, Asmaul Husna, Tahlil Istighotsah, Wirid Surah As-Sajadah, and Al-Mulk, which aim to shape the religious behavior of Pondok Pesantren Riyadlul Jannah students. So that the creation of self-adjustment between humans and themselves and their environment, based on faith and piety and aims to achieve a meaningful and happy life in this world and in the hereafter. The purpose of this research is to find out how the influence of dzikir on the religious behavior of the Pondok Pesantren Riyadlul Jannah students which is carried out for students. This research is an ex post facto research, which is a research model where the main data is put forward after something has happened. This study uses a quantitative approach with Product Moments correlation analysis. From this research, it can be concluded that the effect of dzikir that is carried out on the religious behavior of students is to create a calm and serene feeling so that the students in facing problems are calmer, the application of dzikir to the religious behavior of students in the Pondok Pesantren Riyadlul Jannah is mostly included in the moderate category 95 %, 4% high, and a low 1% category. The increase in dzikir towards the religious behavior of the Pondok Pesantren Riyadlul Jannah Pacet Mojokerto students was mostly in the medium category, 62%, 30% high, and a small part in the low 8% category. There is a positive and significant influence between the influence of dzikir on the religious behavior of students at the Pondok Pesantren Riyadlul Jannah Pacet Mojokerto.